Professional learning standards in practice: a study of how the standards develop professional capital and collective efficacy in mid-career teachers during change - Hurla, Laura Ellen (Kansas State University, 2023)
In the spring of 2022, Learning Forward released an updated version of their professional learning standards. The concepts and research highlighted in the 2022 version of the standards are not necessarily new to the field of education. However, orchestrating the standards to create conditions for success and enact transformational processes for teacher learning and student achievement can be challenging. Combine that challenge with the stress of a global pandemic and rapid changes in public education, and the impact on teachers is significant. This interview study explored the results of applying the concepts underscored in the 2022 Standards for Professional Learning on the professional capital and collective efficacy of mid-career teachers. This study engaged four mid-career teachers, two administrators, and two professional learning trainers in interviews and focus groups. Each participant was instrumental in a Midwestern elementary school’s professional learning and development process for becoming the first Quantum Learning Distinguished School in the United States. The participants shared their perspectives on their professional learning experiences guided by leadership. The interviews and focus groups were coded for intersecting themes. The mid-career teachers and leaders involved in the study confirmed the concepts included in the 2022 Standards for Professional Learning. The emerging themes were ongoing, connected professional learning with consistent positive feedback and collaboration, as well as showcasing the need for leaders to maintain quality communication, a shared vision, and a focus on change. It was evident that mid-career teachers need to feel a strong sense of belonging in the school culture to continue to blossom in professional capital. This study highlights what mid-career teachers value when undergoing high levels of stress, such as the Covid-19 Pandemic while thriving in professional learning settings. Leaders can reference this study to better understand how to create a culture to support the growth of mid-career teachers.
Keywords: Mid-career teachers; Professional development; Professional learning standards; Professional capital; Collective teacher efficacy; Covid-19